CpG Motifs in Porphyromonas gingivalis DNA Stimulate Interleukin-6 Expression in Human Gingival Fibroblasts - Takeshita, Akira (American Society for Microbiology, 1999)
We suggest here that Porphyromonas gingivalis DNA may function as a virulence factor in periodontal disease through expression of inflammatory cytokine. The bacterial DNA markedly stimulated in a dose-dependent manner interleukin-6 (IL-6) production by human gingival fibroblasts. The stimulatory action was eliminated by treatment with DNase but not RNase. The stimulatory effect was not observed in the fibroblasts treated with eucaryotic DNAs. The bacterial DNA also stimulated in dose- and treatment time-dependent manners the expression of the IL-6 gene in the cells. In addition, the stimulatory effect was eliminated when the DNA was methylated with CpG motif methylase. Interestingly, a 30-base synthetic oligonucleotide containing the palindromic motif GACGTC could stimulate expression of the IL-6 gene and production of its protein in the cells. Furthermore, the synthetic oligonucleotide-induced expression of this cytokine gene was blocked by pyrrolidine dithiocarbamate and N-acetyl-l-cystine, potent inhibitors of transcriptional factor NF-κB. Gel mobility shift assay showed increased binding of NF-κB to its consensus sequence in the synthetic oligonucleotide-treated cells. Also, using specific antibody against p50 and p65, which compose NF-κB, we showed the consensus sequence-binding proteins to be NF-κB. These results are the first to demonstrate that the internal CpG motifs in P. gingivalis DNA stimulate IL-6 expression in human gingival fibroblasts via stimulation of NF-κB.